The Effects of Zataria Multiflora Hydroalcoholic Extract on Some Liver Enzymes, Cholesterol, Triglyceride, HDL-Cholesterol, LDL-Cholesterol, Albumin and Total Protein in Rat - Ameneh Khoshvaghti; Saeed Nazifi; Seena Derakhshaniyan; Bijan Akbarpour (Journal of Basic & Applied Sciences, 2012)
Zataria multiflora is a valuable medicinal plant grown extensively in Iran, Pakistan and Afghanistan. The chemical compositions of their extracts have been extensively characterized in Iran and Pakistan. The present study was undertaken to investigate the effects of Zataria multiflora on some liver enzymes, triglyceride, cholesterol, HDL-cholesterol, LDL-cholesterol, albumin and total protein in rat. Sixty adult male Wistar rats weighing about 200 to 220 g were divided into six groups of ten. The control group (group 1) did not receive any drug. The sham group (group 2) received 2 cc of distilled water. The other four experimental groups (groups 3 to 6) including very low (100 mg/kg BW), low (200 mg/kg BW), medium (300 mg/kg BW) and maximum dose (400 mg/kg BW) received Zataria multiflora hydroalcoholic extract intraperitoneally daily for 28 days. After 28 days all animals in the different groups were weighed and blood samples were collected from heart vein. Serum biochemical parameters were measured using validated standard methods. The results of this study showed Zattaria multiflora hydroalcoholic extract analyses various lipids in lipid tissues and transfer to blood for elimination from body.